2013
DOI: 10.1542/peds.2012-3844
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Air Pollution, Maternal Psychological Distress, and Child Behavior

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Prenatal exposures to diverse pollutants and psychosocial stressors have been shown independently to adversely affect child development. Less is known about the potential interactions between these factors, although they commonly co-occur, especially in disadvantaged populations. WHAT THIS STUDY ADDS:The combination of high prenatal exposure to environmental polycyclic aromatic hydrocarbons and maternal demoralization adversely affects child behavior, and maternal demoralization h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 63 publications
1
61
0
1
Order By: Relevance
“…Initial title and abstract screening identified 32 candidate studies, and they were all assessed for eligibility: one study was excluded because of indoor exposure (13) and another one because it only provided interaction values between prenatal exposure to airborne PAHs and maternal psychological distress during pregnancy on subsequent behavioral problems in children (14). An additional study was found in MEDLINE but not through the keyword search (15).…”
Section: Search Resultsmentioning
confidence: 99%
“…Initial title and abstract screening identified 32 candidate studies, and they were all assessed for eligibility: one study was excluded because of indoor exposure (13) and another one because it only provided interaction values between prenatal exposure to airborne PAHs and maternal psychological distress during pregnancy on subsequent behavioral problems in children (14). An additional study was found in MEDLINE but not through the keyword search (15).…”
Section: Search Resultsmentioning
confidence: 99%
“…The questionnaire included questions on, but was not limited to, demographics (e.g., age, sex), lifestyle factors (e.g., exposure to environmental tobacco smoke), socioeconomic status (e.g., maternal education, occupation, household income), medical history, as well as a 27-item questionnaire, Psychiatric Epidemiology Research Instrument – Demoralization (Peri-D) to assess maternal demoralization (Clarke and Kissane, 2002; Dohrenwend et al, 1980), a standard measure of maternal psychologic distress (Perera et al, 2013). The questionnaire also ascertained dietary habits for foods (poultry, beef, pork, sausage) likely to contain PAH (e.g., type of cooking process (smoked, fried, broiled, and barbecued) for specific types of meat, and the frequency at which they consumed those food items ranging from “never” to “daily”); similar tools have shown to be valid instruments for measuring dietary PAH exposure (John et al, 2011; Sinha et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…For example, higher prenatal PAH exposure was inversely associated with measures of fetal growth, such as birth weight and head circumference, and neurodevelopment outcomes in children (Jedrychowski et al, 2003). Within two birth cohorts in the United States and Poland, prenatal PAH exposure was associated with poor cognitive development and intelligence, as well as behavioral problems, in children measured at three to seven years of age (Edwards et al, 2010; Perera et al, 2009; Perera et al, 2006; Perera et al, 2012; Perera et al, 2013). Given the potential long term consequences of prenatal and early life exposure to PAH, reduction of exposure to PAH and identification of modifiable risk factors that modulate downstream effects of PAH exposure are crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we focus this review on those two exemplar exposures, though the range of chemical exposures to which this model of stressrelated susceptibility may apply is undetermined, and may include non-environmental exposures, including the common cold virus [26] or psychotropic drugs [27]. Finally, we focus here on results related to physical health outcomes, including respiratory and cardiovascular disease, and mortality, but note hypothesized synergistic effects on behavioral, mental health, and cognitive outcomes [24].…”
Section: Methodsmentioning
confidence: 99%